15 August, 03:16
Solve 3 (x-5) - 4 (x+3) =
15 August, 03:40
3 (x-5) - 4 (x+3)
Multiply the first bracket by 3
(3) (x) = 3x
(3) (-5) = -15
(-4) (x) = -4x
(-4) (3) = -12
3x-4x-15-12 (combine like terms)
Answer: - x-27
Know the Answer?
Not Sure About the Answer?
Find an answer to your question 👍
“Solve 3 (x-5) - 4 (x+3) = ...”
in 📗 Mathematics if the answers seem to be not correct or there’s no answer. Try a smart search to find answers to similar questions.
Search for Other Answers
You Might be Interested in
Choose the right answer. To calculate the number of pounds of meat required to feed diners do the following: for poultry or meat with bones, divide the number to be served by 2.5; for meat with little or no bone, divide the number to be served by 3.
8.260 in expanded word form
The perimeter of a square is 26.46 inches. What is the side length of the square?
Right a real world problem that compares the ratios 5 to 9 and 12 to 15
What is the solution to the equation? 14g=154
New Questions in Mathematics
2.57142857 as a fraction
Convert 7 pounds 3 ounces to kilograms. Conversion ratios: 1 lb = 16 oz 1 kg = 2.2 lb
2x+7-5x+8=3 (5+6x) - 12x
Of the marbles in a bag, 4 are yellow, 5 are blue, and 4 are red. Sandra will randomly choose one marble from the bag. Fill in the blanks in parts a and b. a. The probability that Sandra will choose a red marble from the bag is out of 17 or
How do I solve for B in the formula I=M/B+a Is this correct: B=M/I - a
» Solve 3 (x-5) - 4 (x+3) =